Neuroprotective Effect of Moxibustion on Cerebral Ischemia/Reperfusion Injury in Rats by Downregulating NR2B Expression - Zhong Di (Hindawi Limited, 2021)
Objective. Stroke is a common and frequently occurring disease of the central nervous system, which is characterized by high mortality and a high disability rate. Moxibustion is a common method for treating stroke in traditional Chinese medicine, but its neuroprotective mechanism is unknown. N-Methyl-D-Aspartate Receptor Subunit 2B (NR2B) plays an important role in neuronal apoptosis. The objective of this study was to explore the mechanisms underlying the neuroprotective effect of moxibustion on cerebral ischemia/reperfusion (I/R) injury based on NR2B. Methods. Sprague–Dawley rats were randomly divided into 5 groups: the control group, I/R group, I/R + moxibustion group, I/R + Ro25-6981 (NR2B antagonist) group, and I/R + Ro25-6981 + moxibustion group. The cerebral ischemia/reperfusion model was induced by middle cerebral artery occlusion. Before the establishment of the model, the Ro25-6981 group received intraperitoneal injections of Ro25-6981, the moxibustion group received moxibustion, and the Ro25-6981 + moxibustion group received both interventions. The neurological dysfunction was evaluated by a neurological deficiency score (NDS). The infarct volume was examined by TTC (2,3,5-triphenyltetrazolium chloride) staining. The apoptosis rate of cerebral cells in the ischemic area was examined by TUNEL (terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling) staining, and the expression of Bcl-2, Bax, and caspase-3 was observed by western blot. NR2B and JNK were also observed by western blot. Results. Compared with the I/R group, moxibustion significantly decreased the neurological deficiency score (P < 0.05) and the infarct rate (P < 0.01) in I/R rats which were similar to those in the Ro25-6981 group. After moxibustion treatment, there was a significant decrease in the apoptosis rate (P < 0.001) and the protein expression levels of Bax, caspase-3, and JNK (P < 0.001) and an increase in the expression of Bcl-2 (P < 0.01). Compared with the I/R group, moxibustion downregulated the expression of NR2B and decreased the activity of NR2B in the cerebral ischemia area (P < 0.001). Conclusions. Moxibustion can improve neurological dysfunction and decrease infarction area and neuronal apoptosis caused by cerebral ischemia/reperfusion in rats. Its neuroprotective mechanism may be related to downregulating the expression of NR2B.